(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
In the Kokand Khanate, the development of librarianship and the art of manuscript production flourished under the consistent attention of its rulers. The presence of a designated librarian in the Kokand palace indicates that the rulers maintained exclusive libraries within their palaces. Some Kokand khans showed a profound interest in handwritten books and libraries in general, and information is provided about their patronage of poets and writers